The Effects of Capital Income Taxation on International Competitiveness and Trade Flows - Bovenberg, A. Lans (American Economic Review, 1989)
Using an intertemporal equilibrium model, this paper analyzes how lower source-based taxes on capital income impact trade performance and international competitiveness. It shows that, depending on import shares and intertemporal and intratemporal substitution elasticities, capital accumulation may induce changes in real interest rates and the terms of trade that stimulate domestic saving–even if financial capital is perfectly mobile internationally. Import shares appear important determinants of exchange rate effects. Numerical simulations illustrate these results.